Transformasi Digital, Stabilitas Politik-Ekonomi, dan Kompromi Kebijakan Pembangunan dalam Jalur Pertumbuhan Indonesia: Analisis Kualitatif - Sri Marlia; Titania Mukti; Ahyakudin; Sujai Saleh (Yayasan Penelitian dan Pengabdian Masyarakat Sisi indonesia, 2026)
Indonesia’s economic growth during the 2020–2026 period reflects a post-pandemic recovery process supported by accelerated digital transformation and relative political stability. However, economic growth has remained at around 5 percent and has not yet reached higher long-term development targets. This study aims to analyze the role of digital transformation and political stability in shaping Indonesia’s economic growth trajectory, identify the opportunities and challenges of digitalization, and evaluate the effectiveness of development policies implemented during the 2020–2026 period. This research employs a qualitative approach using a case study method. Data were collected through documentary analysis and literature review from various sources, including government reports, policy documents, academic publications, and institutional datasets related to digital transformation, political stability, and economic development. The data were analyzed using thematic analysis through the stages of data reduction, categorization, interpretation, and conclusion drawing. The findings indicate that digital transformation contributes to improvements in productivity, economic efficiency, financial inclusion expansion, and MSME competitiveness. These impacts are reinforced by infrastructure development policies implemented primarily before 2025, including the construction of the National Capital City (IKN), roads, and dams, which strengthen regional connectivity and economic integration. Meanwhile, during the 2025–2026 period, the implementation of the Free Nutritious Meal Program (Makan Bergizi Gratis/MBG) and the strengthening of the Red and White Cooperative (Koperasi Merah Putih) reflect a policy orientation toward inclusive development and grassroots economic empowerment, although they also increase fiscal financing requirements. From a macroeconomic perspective, rising fiscal commitments may influence market risk perceptions, reflected in exchange rate volatility of the Indonesian rupiah and fluctuations in capital market performance. Political stability remains a key determinant in maintaining investor confidence and ensuring policy continuity. The study concludes that the synergy between digital transformation, political stability, and development policy trade-offs constitutes a critical determinant of Indonesia’s inclusive and sustainable growth trajectory.